New Book: Tropical Forest Fruits, Seeds, Seedlings and Trees - Ng, F.S.P. (UTAR Agriculture Science Journal, 2015)
A 430-page book on fruit and seed recognition, germination characteristics, seedling growth, tree architecture, and post-architectural development.